Comment on August 12, 1999, Oxnard Airport Authority Agenda Item 5.B. and Request for Continuance - Richard J. Maggio:::::: (1999)
Correspondence discussing issues related to the Revised Draft Oxnard Airport Master Plan and Final Environmental Impact Report.